1994
DOI: 10.1017/s0954102094000507
|View full text |Cite
|
Sign up to set email alerts
|

Survival of faecal bacteria in Antarctic coastal waters

Abstract: The effect of solar radiation on the survival of Escherichia coli, Salmonella zanzibar and a faecal Streptococcus strain in seawater was tested in laboratory experiments, and survival of E. coli was tested under natural light conditions at Davis Station, Antarctica. Exposure to artificial light of wavelengths 290–800 nm caused a rapid decline in viability of each strain examined. T90 values (the time taken for 90% of the population to be inactivated) were ~50 min, 40 min and 2 h for E. coli, S. zanzibar and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…This and other studies (40,44) have shown the bactericidal effect of solar radiation on a range of sewage microorganism species. Various factors affect the cytotoxic effect of solar radiation on fecal coliforms.…”
Section: Seasonal Variation In Physical and Biological Parameterssupporting
confidence: 75%
See 1 more Smart Citation
“…This and other studies (40,44) have shown the bactericidal effect of solar radiation on a range of sewage microorganism species. Various factors affect the cytotoxic effect of solar radiation on fecal coliforms.…”
Section: Seasonal Variation In Physical and Biological Parameterssupporting
confidence: 75%
“…Fecal bacterial survival rates can vary from a few minutes to many days depending upon the environmental conditions (44). Physical factors affecting the survival of fecal microorganisms in seawater include solar radiation (16,27,28,39,43), temperature (37,41), and salinity (1,35).…”
mentioning
confidence: 99%
“…101,108 To complicate matters, however, natural variations in environmental factors such as algal blooms, salinity, water depth, sea-ice formation, and solar radiation can significantly alter the number of viable microbial sewage indicators detected. 101,114 As an example, the ability of solar radiation to deactivate fecal coliform bacteria in Antarctica is enhanced with increasing exposure time and decreasing radiation wavelength, ozone-column depth, cloud cover, and solar-zenith angle. 115 Although they are essential for the purpose of risk assessment, studies of the impacts of sewage pollution on marine biotas have been performed near only a few Antarctic outfalls.…”
Section: Chemical Pollution From Research Stationsmentioning
confidence: 99%
“…The extent of sewage pollution is influenced by the number of people on station generating the waste, 108,110,111 the efficiency of any treatment facility, 98,112,113 and physiographic features affecting dispersal and dilution rates 101,108 . To complicate matters, however, natural variations in environmental factors such as algal blooms, salinity, water depth, sea‐ice formation, and solar radiation can significantly alter the number of viable microbial sewage indicators detected 101,114 . As an example, the ability of solar radiation to deactivate fecal coliform bacteria in Antarctica is enhanced with increasing exposure time and decreasing radiation wavelength, ozone‐column depth, cloud cover, and solar‐zenith angle 115 …”
mentioning
confidence: 99%
“…Faecal coliform dynamics in coastal waters is a function of bacterial loading from streams and rivers, mass transport, and bacterial losses due to death and sedimentation. Faecal bacterial survival rates can vary from a few minutes to many days depending upon the environmental conditions (Statham & McMeekin, ). Their disappearance rates from surface waters depend on a number of factors such as the availability of nutrients, temperature, salinity, turbidity, degree of water mixing, solar radiation, predation, and competition (Auer & Niehaus, ; Flint, ; Hood & Ness, ).…”
Section: Introductionmentioning
confidence: 99%